O papel da lei complementar nos tributos sobre a transmissão causa mortis e doação - Cury, Fabio Lemos (2021)
The purpose of this paper is to study the role of supplementary law on the regulation of Estate and Gift Tax (ITCMD). To this effect, an outline is made of some conceptual assumptions on the general theory of law and constitutional tax law, such as our concepts of law, rules and their systematic nature, determined by fundamental principles and rights. An analysis is made of the concepts of competence, especially tax competence and the role of supplementary law as a regulatory definition capable of creating centralizing elements that strengthen the consistency and accordance among the federative orders, which is achieved through: (i) provisions on conflicts of competence in tax matters; (ii) regulation on constitutional limitations to the powers to tax; and (iii) establishment of general rules on tax legislation. Hence, supplementary laws are a mechanism which as an effect of the Federal Constitution, represents the Brazilian tax federalism. With such assumptions, the matrix rules on estate and gift taxes are outlined to point out the extent to which the supplementary laws contribute – or should contribute – to mitigate issues and discrepancies regarding these taxes. Some of the controversial issues in the regulation of said taxes by state legislations are pointed out, reflecting the deficient regulation of the supplementary law on such taxes. Despite such deficiency in the legislation, the general framework whereby the National Tax Code (CTN) allows the settlement of disputes regarding ITCMD is envisaged. Lastly, trust and joint tenancy with rights of survivorship are examined to determine the possible levy of ITCMD on certain cases involving such doctrines, always in light of supplementary law